In vitro Controlled Release from Solid Pharmaceutical Formulations of two new Adamantane Aminoethers with Antitubercular Activity (I). - Vlachou, Marilena; Siamidi, Angeliki; Diamantidi, Evanthia; Iliopoulou, Alexandra; Papanastasiou, Ioannis; Ioannidou, V.; Kourbeli, Violeta; Foscolos, Angeliki-Sofia; Vocat, Anthony; Cole, Stewart T.; Karalis, Vangelis; Kellici, Tahsin; Mavromoustakos, Thomas (Drug Research, 2017)
The aim of the present investigation was to develop matrix tablet formulations for the in vitro controlled release of 2 new tuberculocidal adamantane aminoethers (compounds I and II), congeneric to the adamantane derivative SQ109, which is in final clinical trials, using carefully selected excipients, such as polyvinylpyrrolidone, sodium alginate and lactose. The tablets were prepared using the direct compression method and dissolution experiments were conducted using the US Pharmacopoeia type II apparatus (paddle method) in gastric and intestinal fluids. The results confirm that both analogues, albeit more lipophilic than SQ109, showed satisfactory in vitro release characteristics from solid pharmaceutical formulations. In conclusion, these formulations merit further assessment by conducting in the future bioavailability in vivo studies.
Keywords: 1,3-Bis[4-(2-morpholinoethoxy)phenyl]adamantane; 2,2-Bis[4-(2-morpholinoethoxy)phenyl]adamantane; antituberculars; drug delivery